2014
DOI: 10.1097/jom.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Medical Evacuations From Oil Rigs off the Gulf Coast of the United States From 2008 to 2012

Abstract: Illness, not occupational injuries, is identified as the major reason for medical evacuations from oil rigs. Heart disease is the leading cause of chronic health conditions resulting in a medevac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 13 publications
1
24
0
4
Order By: Relevance
“…The few reports published for offshore oil and gas, and for the wind industry showed that the majority of illnesses were musculoskeletal in nature (Norman et al 1988; Ponsonby et al 2009; Thibodaux et al 2014; Jürgens and Weinrich 2015). Musculoskeletal injuries are accountable for more missed workdays than any other form of illness for all occupations and have long been shown to be related to physical fitness (Rayson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The few reports published for offshore oil and gas, and for the wind industry showed that the majority of illnesses were musculoskeletal in nature (Norman et al 1988; Ponsonby et al 2009; Thibodaux et al 2014; Jürgens and Weinrich 2015). Musculoskeletal injuries are accountable for more missed workdays than any other form of illness for all occupations and have long been shown to be related to physical fitness (Rayson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to limited resources and extended time for medical interventions, there is an added cost burden that occurs in the event of emergency services or transport. In a review of medical evacuations from oil rigs off the Gulf Coast of the United States, Thibodaux reported that the average cost of a medical evacuation was $49,250, which did not account for any medical treatment onshore, lost productivity, or replacing the employee's position (Thibodaux et al, 2014). As shown in Table 1 below, the majority (77%) of medical evacuations were for non-occupational injuries or illnesses, with more than half primarily related to cardiovascular causes.…”
Section: Industry Relevance -Us Gulf Coast Examplementioning
confidence: 99%
“…In addition to the financial implications of these incidents, health and wellness personnel also reported safety concerns related to the numerous night-time flights . Recommendations for addressing the high financial and human capital costs include proactive institution of appropriate fitness for duty, pre-placement and periodic medical evaluations, as well as preventive wellness programming (Thibodaux et al, 2014).…”
Section: Industry Relevance -Us Gulf Coast Examplementioning
confidence: 99%
“…The most common cause for ferry helivacs were heart-related symptoms (40%), which corresponds to a study of 397 helivacs of workers from 202 oilrigs off the United States gulf Coast in 2002-2012 (cardiovascular diseases: 26-45%) [10]. Similarly, 35% of 104 critically ill patients airlifted to a Florida hospital from cruise ships in the Caribbean in 1999-2000 had heart conditions [11].…”
Section: Thor-erik Holt Et Al Medical Emergencies On Large Passengementioning
confidence: 99%